2010
DOI: 10.1128/aem.02317-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Main Promoter Directing Cereulide Biosynthesis in Emetic Bacillus cereus and Its Application for Real-Time Monitoring of ces Gene Expression in Foods

Abstract: Cereulide, the emetic Bacillus cereus toxin, is synthesized by cereulide synthetase via a nonribosomal peptide synthetase (NRPS) mechanism. Previous studies focused on the identification, structural organization, and biochemical characterization of the ces gene locus encoding cereulide synthetase; however, detailed information about the transcriptional organization of the ces genes was lacking. The present study shows that the ces-PTABCD genes are transcribed as a 23-kb polycistronic transcript, while cesH, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
83
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 64 publications
(69 reference statements)
4
83
0
1
Order By: Relevance
“…Cereulide is produced by a clonal lineage of B. cereus strains that carry a pXO1-like megaplasmid, termed pBCE, which encodes the cereulide synthetase (ces) NRPS (14,16). Recently, we showed that the ces gene cluster is polycistronically transcribed from a central promoter in a strict temporally regulated way (12,13).…”
mentioning
confidence: 99%
“…Cereulide is produced by a clonal lineage of B. cereus strains that carry a pXO1-like megaplasmid, termed pBCE, which encodes the cereulide synthetase (ces) NRPS (14,16). Recently, we showed that the ces gene cluster is polycistronically transcribed from a central promoter in a strict temporally regulated way (12,13).…”
mentioning
confidence: 99%
“…These elements contain a 23-kb gene cluster (ces) involved in the cereulide synthesis. The two largest genes, named cesA (ϳ10 kb) and cesB (ϳ8 kb), lead to the incorporation and modification of D-O-Leu, D-Ala (cesA), L-O-Val, and D-Val (cesB), which compose the basic tetradepsipeptide motif of cereulide (7,14).…”
mentioning
confidence: 99%
“…These elements contain a 23-kb gene cluster (ces) involved in the cereulide synthesis. The two largest genes, named cesA (ϳ10 kb) and cesB (ϳ8 kb), lead to the incorporation and modification of D-O-Leu, D-Ala (cesA), L-O-Val, and D-Val (cesB), which compose the basic tetradepsipeptide motif of cereulide (7,14).Cereulide can cause stomach pain and vomiting, respiratory distress, and occasional loss of consciousness, possibly leading to coma and ultimately death of the individual (6). This toxin is also an ionophoric molecule with a high degree of affinity for K ϩ ions (26).…”
mentioning
confidence: 99%
“…Cereulide is a so-called cyclic dodecadepsipeptide containing a three-repeat sequence [cyclo(L-O-Val-L-Val-D-O-Leu-D-Ala-)3], and its K ϩ ionophoric properties have been established in black-lipid membranes and by assessing its impact on mitochondrial swelling and function (1,32,45,68). Recent research focused mainly on the genetic factors involved in the production of cereulide, the identification of transcriptional regulators, detection methods, and the impact of environmental conditions on cereulide levels reached, including a variety of (model) foods (13,15,17,38,69,71,78). Yet, besides its role in food poisoning and its effect on mammalian cells, the biological relevance of cereulide production in the environment, including its impact on other bacteria, has not been addressed.…”
mentioning
confidence: 99%
“…Recent research focused mainly on the genetic factors involved in the production of cereulide, the identification of transcriptional regulators, detection methods, and the impact of environmental conditions on cereulide levels reached, including a variety of (model) foods (13,15,17,38,69,71,78). Yet, besides its role in food poisoning and its effect on mammalian cells, the biological relevance of cereulide production in the environment, including its impact on other bacteria, has not been addressed.…”
mentioning
confidence: 99%